Dental Occlusion as A Health Risk for Visual Acuity in Relation to Salivary Transforming Growth Factor Beta-1 ( TGF-Β1) Among Students Aged 8-10 Years - A. Ajeel Alrikabi, Noor; S. Diab, Ban (Journal of the Faculty of Medicine Baghdad, 2024)
Background: Correct mouth function is one of the functional matrices that contribute to the growth of the maxilla, which is connected to the growth of orbit, and vice versa. Objective: to ascertain how dental malocclusion affects the visual acuity-related salivary transforming growth factor beta-1 (TGF-β1). Patients and Methods: This is a cross-sectional study on 653 students, 8–10 years of age from elementary schools in the governorate of Al-Diwaniyah during the period from 1st of November 2022 to 30th March 2023. Using the Snellen E chart and Angle’s classification to identify malocclusion, they were subjected to visual-capacity testing for refractive disorders. Sub-samples were selected from the normal and visually impaired groups for salivary transforming growth factor beta-1 salivary analysis measurement. Results: Only 70 out of 653 students were found to have reduced visual acuity. When compared to students with normal visual acuity, they had significantly higher levels of salivary transforming growth factor beta-1. Those with reduced visual acuity were found to have a much higher occurrence of dental malocclusion utilizing molar’s relation of Angle’s categorization. Conclusion: The students with impaired visual acuity were more likely to have dental malocclusions and increased levels of TGF-β1.